Boltzmann equation studies of the off-equilibrium QCD phenomena - Viljoen, Brandon (Department of Physics, 2016)
Much of the evolution of the quark-gluon plasma (QGP) produced in heavy-ion collisions can be modeled by relativistic (viscous) hydrodynamics, which assumes that the partons are sufficiently close to equilibrium. We would like to explore the dynamics of QGP, even before this (quasi) equilibrium stage is reached. To that end, a useful tool from the stage where we can assume the partons to be on-shell is the relativistic Boltzmann equation. We develop parallel code to solve the relativistic Boltzmann equation in the relaxation time approximation in 3 + 1 dimensions (without simplifying assumptions on possible symmetries of the dynamics). Our approach, solving for the distribution function, will allow us to obtain detailed information about the dynamics of heavy ion collisions beyond hydrodynamics, which specify only bulk properties of the medium. Following recent work, we also explore the possibility of forming a transient Bose-Einstein condensate in a dense system of gluons, such as those found in the early stage of a heavy ion collision. For simplicity, we focus here on purely gluonic systems (without quark degrees of freedom). We first use our code to describe a system undergoing 0 + 1 longitudinal Bjorken expansion, after which we present some first numerical results for a system in the full 3 + 1 dynamics.